ҚАРАҚАЛПАҚ ТИЛИНИҢ ТҮСИНДИРМЕ СӨЗЛИГИНДЕ ОМОНИМ СӨЗЛЕРДИҢ БЕРИЛИЎИ - Мамбетмуратова, М.Т. (SCIENCE and SOCIETY, 2020)
The spelling dictionary of the Karakalpak language speaks about the giving of homonymous words, attention to their meanings and etymology.
Keywords: semantics; homonymy; visual material; word; vocabulary